HUBUNGAN PENGETAHUAN, SIKAP, DAN DUKUNGAN PENGELOLA TERHADAP KESIAPSIAGAAN PEDAGANG DALAM UPAYA PENCEGAHAN KEBAKARAN DI PASAR SEMAWIS KOTA SEMARANG - Wenta Chris Omega Manik; Bina Kurniawan; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2020)
Fire is a situation that can cause extraordinary losses. So, fire prevention is needed especially preparedness in fire prevention efforts. Semawis Market is a tourist attraction that has become an icon of Semarang City that needs to be preserved and sustainable. But in its activities, Semawis Market has a high risk of fire seen from the activities in Semawis Market, the layout and the density of visitors who visit it. The purpose of this study is to provide an overview of Semawis Market and find the relationship between knowledge, attitudes, and support of management to the preparedness of traders in efforts to prevent fire in the Semarang City Semawis Market. The research used analytic research using quantitative methods with cross sectional approach. The population in this study were 130 traders in the Semawis Market. The sample in this study amounted to 70 people who were selected based on the purposive sampling method which was then analyzed by chi-square statistical analysis. Questionnaire was used as instrument in this study. The results.of the univariate analysis of this study were 77.1% respondents have good knowledge, 82.9% respondents have good trade, respondents agreed that management support is well was 52.9% and 61.4% respondents have good preparedness. Bivariate analysis results in this study indicate that there is a relationship between knowledge (p = 0.025) and attitude (p = 0.028) with preparedness and there is no relationship between management support (p = 0.264) with preparedness. Traders need to prepare themselves and equipment better to prevent fires as well as the need for more tangible management support in preparedness actions.